Quality Rejected Roast Chicken with Yellow Seasoning and Addition of Bromelain Enzyme - Fajri Rahman; Lise Asnur (Universitas Negeri Padang, 2025)
This study aimed to analyze the effect of bromelain enzyme addition on the quality of grilled spent hen with yellow seasoning in terms of shape, color, texture, aroma, and taste. This research was a true experimental study with a one-factor design consisting of four treatments: without pineapple addition (P0), 250 g pineapple/kg (P1), 500 g pineapple/kg (P2), and 750 g pineapple/kg (P3). The organoleptic evaluation was carried out by three expert panelists using a 1–4 rating scale.The Mann-Whitney test results showed that the addition of bromelain had a significant effect on texture (p<0.05) and taste (p<0.05), but no significant effect on shape, color, and aroma (p>0.05). The best treatment was obtained at a concentration of 500 g pineapple/kg (P2), producing grilled chicken with an intact shape, attractive golden-brown color, tender texture, fresh aroma combining spices and pineapple, and well-balanced savory taste. These findings indicate that bromelain enzyme effectively improves the physical and organoleptic qualities of spent hen meat, thereby enhancing its market value and consumer acceptance.